2018
DOI: 10.1080/01612840.2018.1463326
|View full text |Cite
|
Sign up to set email alerts
|

Providing a Safe Environment in a Psychiatric Ward: Nurses and Vigilance in Iran

Abstract: The aim of this study was to explore nurses' use of vigilance in the provision of inpatient psychiatric care. In this qualitative exploratory descriptive design study, 16 nurses working in inpatient psychiatric units were recruited through purposive sampling. Data were collected by semi-structured interviews and fieldwork observations and analysed using conventional content analysis. According to participants, nurses' vigilance is related to synthesising knowledge, experience, communication, and presence. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Other studies using different scales to assess nursing vigilance and patient safety have also reported high vigilance levels in the performance of daily nursing care. For example, Vahidi et al [6] conducted interviews with nurses working in psychiatric wards and showed that nurses were able to predict events and take appropriate preventive measures by cognitively evaluating patients through the assimilation of data from their observations and available risk assessment patterns. Additionally, O'Brien et al [19] explained that nurses in the recovery room reduced risk and ensured patient safety using team and instant coordination strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies using different scales to assess nursing vigilance and patient safety have also reported high vigilance levels in the performance of daily nursing care. For example, Vahidi et al [6] conducted interviews with nurses working in psychiatric wards and showed that nurses were able to predict events and take appropriate preventive measures by cognitively evaluating patients through the assimilation of data from their observations and available risk assessment patterns. Additionally, O'Brien et al [19] explained that nurses in the recovery room reduced risk and ensured patient safety using team and instant coordination strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Vigilance is a largely invisible but essential element of intensive care nursing [4]. The term "vigilance" is derived from the old French word "vigilia", meaning a state or practice of being careful about potential dangers or problems [6]. Loeb and Alluisi [7] introduced vigilance in their signal recognition theory and characterized vigilance as a search for signals when the events construed by individuals as important occur in a noisy background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29,30] While some clinical trials and published articles showed the effectiveness of reflective debriefing among healthcare workers such as nurses, the decision to undergo such treatment must be within the nurse' voluntary resolve or as required and provided by the organization's policies and by-laws. [5] In China, the Chinese version of the Psychosocial Safety Climate Scale or PSC-12 recommended the need to promote safety classes and trainings among nurses to minimize workplace violence or at least nurses will become more equipped in intervening such workplace events. [15] Violence may occur, anywhere and anytime and no one is ever safe from experiencing it.…”
Section: Discussionmentioning
confidence: 99%
“…It highlighted the importance of active listening and assertive involvement in the care of psychiatric patients as it allows a more harmonious interaction between a patient and a nurse thus minimizing occurrence of violent behaviors. [5] Nurses suffer consequential effects of experiencing violence in the workplace. Among the consequences of exposure to these types of violence are physical pain, emotional exhaustion and psychological distress.…”
Section: Introductionmentioning
confidence: 99%